(untitled) (Applied Biological Research, 2023)
This study focused on the development of starch-based nanofibrous scaffolds incorporated with linolenyl alcohol derived from ethanolic extracts of Cayratia trifolia to enhance wound healing. Electrospun nanofibers were fabricated by blending different concentrations of linolenylalcohol (10, 20, and 40% v/v) with starch solutions. The resulting nanofibers were characterized for their morphology, size distribution, thermal stability, FT-IR spectra, and wound healing properties. The nanofibers loaded with linolenyl alcohol exhibited diameters ranging from 73 to 95 nm. Further, these nanofibers displayed improved thermal stability compared to free linolenyl alcohol. FT-IR analysis confirmed the interaction between starch and linolenyl alcohol. When 40% linolenyl alcohol-loaded nanofibers were applied,HaCat cells exhibited increased viability. Western blot analysis revealed elevated levels of vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF) expression, suggesting that the developed nanofibers have the potential to promote angiogenesis and cell proliferation, thus facilitating wound healing. In conclusion, our study demonstrated that electrospun starch-based nanofibrous scaffolds incorporating linolenyl alcohol can effectively accelerate wound healing by activating VEGF and PDGF signaling pathways.